2013
DOI: 10.1097/jcn.0b013e318231f424
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Treatment Practices

Abstract: Brief smoking cessation practices are adequately performed at cardiac wards, but the most effective practices, offering assistance and arranging for follow-up, are less than optimal. The AAR guideline offers a more feasible approach for busy cardiology wards. To ensure successful adoption of this guideline, the heads of cardiac wards should be convinced of its advantages and be encouraged by a supportive work environment. Policies may also facilitate the adoption of the AAR guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 49 publications
5
22
0
Order By: Relevance
“…The telephone and face-to-face counselling intervention had an inpatient and outpatient phase. The inpatient phase incorporated the Ask-Advise-Refer strategy [23, 24] in which patients’ smoking behaviour was assessed, smokers were advised to quit, and referred to outpatients’ smoking cessation counselling, either by telephone or face-to-face. Interventions started within one week of patient enrolment and had a comparable structure and content.…”
Section: Methodsmentioning
confidence: 99%
“…The telephone and face-to-face counselling intervention had an inpatient and outpatient phase. The inpatient phase incorporated the Ask-Advise-Refer strategy [23, 24] in which patients’ smoking behaviour was assessed, smokers were advised to quit, and referred to outpatients’ smoking cessation counselling, either by telephone or face-to-face. Interventions started within one week of patient enrolment and had a comparable structure and content.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported the effectiveness of this strategy in promoting quitting and preventing relapse (Fiore et al, 2008). Some health practitioners who are not trained to provide pharmacotherapy / prescription medications are advised to use the modified version (AAR): Ask about smoking habit, Advice smokers to quit and Refer smoking clients that need assistance to smoking cessation clinics (Berndt et al, 2011). The practice guide also provided action plan for the smoker not ready to quit.…”
Section: Review Of Literaturementioning
confidence: 99%
“…At all levels in both associate degree of nursing and bachelor's degree, the health assessment forms for clinical training contain questions asking if the client smokes cigarette, however, there are no specific questions on shisha and other types of tobacco products. Using the health assessment forms for each of their assigned clients during clinical experience, offers each student the opportunity to 'ask' about smoking habit, 'advice smokers to quit' and 'refer' (AAR) smoking clients that need assistance to smoking cessation clinics as proposed by Berndt et al, (2011), a modification of clinical practice guideline 5As (Ask, Advice to quit, Assist and Arrange quitting methodology proposed by Fiore et al, (2012). The college has a smoking ban policy in the college campus and while on clinical experience in all of its clinical settings.…”
Section: The Research Settingmentioning
confidence: 99%